Does Openness Matter for Financial Development in Africa? - David, Antonio; Mlachila, Montfort; Moheeput, Ashwin (Washington, D.C. : International Monetary Fund, 2014)
This paper analyzes the links between financial and trade openness and financial development in Sub-Saharan African (SSA) countries. It is based on a panel dataset using methods that tackle slope heterogeneity, cross-sectional dependence and non-stationarity, important econometric problems that are often ignored in the literature. The results do not point to a general direct robust link between trade and capital account openness and financial development in SSA, once we control for other factors such as GDP per capita and inflation. But there is some indication that trade openness is more important for financial development in countries with better institutional quality. The findings might be due to a number of factors including distortions in domestic financial markets, relatively weak institutions and/or poor financial sector supervision. Thus, African policy makers should be cautious about expectations regarding immediate gains for financial development from greater international integration. Such gains are more likely to occur through indirect channels.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet